On the Diagnosis of Mycotic Aortic Aneurysms. Issue 12 (19th February 2018) - Sörelius, Karl; di Summa, Pietro G
Objective: There is striking paucity in consensus on the terminology, definition, and diagnostic criteria of mycotic aortic aneurysms. This literature study aims to elucidate this scientific omission, discuss its consequences, and present a proposition for reporting items on this disease. Methods: A systematic literature review on PubMed and Medline using mycotic and infected aortic aneurysms between 1850 and 2017 was performed. Articles were assessed according to a protocol regarding terminology, definition, and diagnostic criteria. Case series with less than 5 patients were excluded. Results: A total of 49 articles were included. The most prevalent term was mycotic aortic aneurysm but there was no widely accepted definition. Most modern publications used a diagnostic workup based on a combination on clinical presentation, laboratory results, imaging findings, and intraoperative findings. How these protean variables should be balanced was unclear. A proposition of reporting items was framed and consisted of definition of disease used, basis of diagnostic workup, exclusion criteria, patient characteristics, laboratory and imaging findings, aneurysm anatomy, details on treatment, pre/postoperative antibiotic treatment, and details on follow-up. Conclusions: This article emphasizes the need to standardize definition, terminology, and diagnostic criteria for mycotic aortic aneurysms and proposes reporting items enhancing comparability between studies.